THU0033 Monitoring Cellular Immune Responses to Influenza Vaccination in Rheumatoid Arthritis Patients: Comparison of Flow Cytometric Analysis of Cytokine Production, Elisa Assay of IFN-Gamma Secretion, and the Granzyme-B Activity Assay. (23rd January 2014) - Madar-Balakirski, N.; Arad, U.; Amir, S.; Mandelboim, M.; Mendelson, E.; Caspi, D.; Elkayam, O.
Abstract : Background: Monitoring of immune responses is essential in a number of clinical research areas that address immunosuppressed individuals, including oncologic and rheumatic patients. During the past 10 years, our group has been deeply involved in the study of vaccinations in rheumatic patients, with a special concern regarding the impact of drugs. While humoral responsiveness is considered the gold standard for most vaccines, including seasonal influenza, evaluation of cellular immune responses is much less standardized, requires specialized equipment and often suffers from technical limitations that eventually lead to inaccurate and inconsistent results. Since cellular response is essential for supporting virus-specific effector cell functions, reliable assessment techniques are of great importance. Objectives: To comparatively assess the cellular immune response to influenza vaccine by 3 different methods, in concomitant with humoral immune response evaluation, in rheumatoid arthritis (RA) patients relative to healthy subjects. Methods: Trivalent influenza subunit vaccine was administered to 18 RA patients treated by synthetic DMARDs, mostly methotrexate (MTX), and to 18 healthy controls. Peripheral blood mononuclear cells (PBMCs) and sera were obtained immediately before and 28 days after vaccination. Three different methods to measure cellular mediated immune responses to influenza vaccination were compared in RA patients and in healthy subjects. These methods included (1) flow cytometric analysis of IL-2 and IFNg production in activated CD4/CD8 T-cells; (2) enzyme-linked immunosorbent assay (ELISA) for the analysis of IFNg secretion and (3) granzyme B activity assay in influenza-stimulated PBMC. The humoral response was evaluated by the hemagglutination inhibition (HI) assay. Results: Cellular response: Vaccination induced a significant increase in PBMC IFNg secretion and Granzyme B activity in the RA patients. A significant increase in Granzyme B activity was also measured in the healthy control group, but there was no change in the levels of secreted IFNg. There was no difference in the frequencies of IFN-g/IL-2 producing activated CD4 or CD8 T-cells, as measured by flow cytometry, in both groups, either before or 4 weeks following influenza vaccination. Humoral response: A significant increase in the geometric mean titer (GMT) of HI was demonstrated for the H1N1 and H3N2 influenza strains in both groups. The response rate to HIN1 was significantly higher in DMARDs patients in comparison with healthy controls. The response rate to the H3N2 and B strains was similar in both groups. Conclusions: The results of this study confirm previous findings on the preserved humoral immune response of RA patients to influenza vaccination. Among the three methods utilized to cellular immune responsiveness - Granzyme B activity assay was the only one to detect such response in both groups tested. It appears that current available measurement methods for cellular responsiveness to influenza vaccination suffer from inconsistency, and are limited in their ability to reflect gained cellular immunity. Disclosure of Interest: None Declared